Un auteur algérien en dialogue avec les fantômes littéraires: L’Imposture des Mots de Yasmina Khadra - Bugert, Ines (Ponti/Ponts, 2021)
In L’Imposture des Mots (2002), the Algerian author Yasmina Khadra enters into dialogue with his literary idols and his favourite fictional characters. Speaking to Kateb Yacine, Malek Haddad, Nazim Hikmet, Friedrich Nietzsche and his literary character Zarathustra as well as to his dead grandfather, an ancient poet, Yasmina Khadra joins their literary tradition without missing to point out his individual position. Introducing Zane and Salah, antagonists of Les Agneaux du Seigneur and À quoi rêvent les loups who literarily pass the fictional frontiers of the novel in order to face their creator in a struggle for posterity and autonomy, Yasmina Khadra relativizes the author’s position in the literary field. In dialogue with those antagonists, the author elaborates and discusses his conception of authorship and criticizes those literary works only striving for commercial profit. Facing his double, officer Moulessehoul, who incarnates the author’s past life as a soldier, reveals the media to be responsible for the role of the writing officer he has to adopt. Finally, his fictional friends, the protagonists of his novels Les Agneaux du Seigneur and Morituri, haj Maurice, Da Achour and Brahim Llob, confront him with his doubts and force him to interrogate his inner conflict. Discussing his conflict with these literary phantoms, Yasmina Khadra manages to see himself in the mirror, to uncover his demons and to shed light on his reality. Yasmina Khadra, auteur algérien, fantômes littéraires, dialogue, revenants littéraires, retour du personnage, maîtres littéraires, littérature maghrébine, conception d’auteur, généalogie littéraire